Understanding the meanings of holy Quran in the rank of phrase - Malik Mustafa Al-Yasiry , Researcher. Hamed; Mutab Tired Al-Masoudi, Prof. Dr. Fadhel (Basra studies journal, 2025)
The current research paper aims at proving that there is a level of understanding for the meanings of the Holy Quran, which is included in the Quranic discourse, and represent the minimum ability of the addressee to understand the intended meanings. It is presented in the clear Quranic style that can be communicated and does not need an interpreter, which is expressed by the statement in the Almighty’s saying: This is an explanation for the people.. (Al Imran: 138), which carries a set of knowledge and sciences that everyone needs, and the general public understands it to the extent that it secures their guidance, not to the extent that they fully need the perfection of guidance, which constitutes a direct responsibility upon them that connects them to the Holy Quran. We reflect this meaning and the effect that results from it in the honorable narrations with different expressions, such as (the scholar and the ignorant know it…. etc..